Assessment of four plant extracts as maize seed protectants against Sitophilus zeamais and Prostephanus truncatus in Ghana - Gariba, Samuel Yakubu; Dzidzienyo, Daniel Kwadjo; Eziah, Vincent Yao (Taylor & Francis, 2021)
Sitophilus zeamais and Prostephanus truncatus can cause weight loss of about 20 to 90% of untreated stored maize seeds. This study assesses four plants (Lantana camara, Moringa oleifera, Citrus sinensis and Hyptis suaveolens) extracts as seed maize protectants against the two insects in Ghana. The study was laid out in a CRD with three replications. Dried powders (5 and 10% w/w) and aqueous extracts (0.05 and 0.1 g/mL) of the botanicals were evaluated for their insecticidal activity with untreated control and Actellic included as checks. Oviposition and survivorship of insects decreased in grains treated with plant extracts. The phytochemical analysis revealed that compounds such as alkaloids, saponins, tannins and phenolic, steroids, flavonoids, anthraquinones, phlobatannins, cardiac glycosides and terpenoids were recorded in all four plant extracts. These compounds may have caused lower progeny emergence, inhibitory effect, repellent action and antifeedant effect to S. zeamais and P. truncatus in grains treated with the botanicals. Maize seeds treated with botanicals after 10 weeks in cribs recorded a reduction in the percentage of seeds damaged and weight loss caused by the two insects compared to the untreated seeds. The study proposes that the botanicals tested, especially H. suaveolens have the potential to enhance quality seed production thereby boosting growth in the seed industry. The botanicals are recommended for use by seed producers and farmers to control P. truncatus and S. zeamais in stored maize seeds.
Keywords: Sitophilus zeamais; Prostephanus truncatus; Lantana camara; Moringa oleifera; Citrus sinensis; Hyptis suaveolens; survivorship; methanol extracts; botanicals; phytochemical; weight loss; Agric; University of Ghana